Metodo rapido y economico para la extraccion de ADN genomico en la broca del cafe y su uso en PCR - Acevedo B, F.E.=700 1 Navarro E, L.; Constantino C, L.M.; Benavides M, P.
(En, Es)
ilus., 9 ref.
Keywords: HYPOTHENEMUS HAMPEI; PCR; ADN; ACIDOS NUCLEICOS; COLOMBIA; CENICAFE